2022
DOI: 10.1371/journal.pgen.1010102
|View full text |Cite
|
Sign up to set email alerts
|

THUNDER: A reference-free deconvolution method to infer cell type proportions from bulk Hi-C data

Abstract: Hi-C data provide population averaged estimates of three-dimensional chromatin contacts across cell types and states in bulk samples. Effective analysis of Hi-C data entails controlling for the potential confounding factor of differential cell type proportions across heterogeneous bulk samples. We propose a novel unsupervised deconvolution method for inferring cell type composition from bulk Hi-C data, the Two-step Hi-c UNsupervised DEconvolution appRoach (THUNDER). We conducted extensive simulations to test T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…To assess deCOOC, we compared it with various state‐of‐the‐art deconvolution algorithms. In addition to Thunder, the sole Hi‐C deconvolution tool published, [ 12 ] we also compared eight transcriptome data‐oriented methods, that is, CS, [ 21 ] CDSeq, [ 17 ] DeconRNAseq, [ 22 ] DSA, [ 16 ] dtangle, [ 23 ] FARDEEP, [ 20 ] NNLS, [ 19 ] and ssKL. [ 26 ] Some tools can take bulk Hi‐C data as input directly, for example, CDseq, while others require additional cell type‐specific genes, for example, DSA and ssKL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess deCOOC, we compared it with various state‐of‐the‐art deconvolution algorithms. In addition to Thunder, the sole Hi‐C deconvolution tool published, [ 12 ] we also compared eight transcriptome data‐oriented methods, that is, CS, [ 21 ] CDSeq, [ 17 ] DeconRNAseq, [ 22 ] DSA, [ 16 ] dtangle, [ 23 ] FARDEEP, [ 20 ] NNLS, [ 19 ] and ssKL. [ 26 ] Some tools can take bulk Hi‐C data as input directly, for example, CDseq, while others require additional cell type‐specific genes, for example, DSA and ssKL.…”
Section: Resultsmentioning
confidence: 99%
“…One way of computationally deriving cell type compositions from bulk Hi-C data involves deconvolution technologies. [9][10][11] To the best of our knowledge, except for Thunder, [12] we have yet to find other algorithms published for Hi-C data deconvolution. Thunder requires a list of predefined marker genes specifically expressed in cell types, that is, cell typespecific genes, while such gene lists are not always available.…”
Section: Introductionmentioning
confidence: 99%
“…Such multi-sample chromatin conformation data have emerged at the bulk level encompassing many cells (Gorkin et al, 2019;Chandra et al, 2021). Cell type deconvolution can be essential when analyzing multi-sample data from tissue samples to ensure valid inference and gain insights in a cell-type-specific manner (Figure 6) (Sefer et al, 2016;Rowland et al, 2022a). We anticipate future studies involving single-cell data, similar to multi-sample single-cell RNAsequencing data (Ren et al, 2021;Zheng et al, 2021), which can provide insights into disease etiology at an even more refined resolution (van Buren et al, 2021(van Buren et al, , 2022Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, joint analysis of scHi-C data with bulk data can also allow us to take advantages of both types of data. For example, Rowland et al [95] identified expected cell-type-specific spatial organization profiles by deconvolving bulk Hi-C data from brain cortex. Naïve application of MUSIC [96] developed for RNA-seq data showed the advantage of integrative analysis with the matched scHi-C data.…”
Section: Single Cell Analysismentioning
confidence: 99%